Determining Reaction Time and Strength in Indonesian Male Badminton Athletes: Regional, National and Olympic Levels - Hari Setijono; Lolita Yuri; Oce Wiriawan; Kunjung Ashadi (OVS LLC, 2024)
Objectives. The study aimed to analyse the difference in whole-body reaction (WBR) times and the expanding strength of badminton athletes at regional, national, and Olympic levels. Materials and methods. The study subjects consisted of 24 male athletes. Audio and visual whole-body reaction measurements were carried out, and each athlete's pull and push strength was expanded to analyse the existing differences. The data was analysed using One-Way ANOVA to determine the differences between the three sample groups. Results. The results showed a significant difference (p < 0.05) in visual whole-body reaction and shoulder arm thrust force. Although, the audio whole body reaction variable and shoulder arm tensile strength did not significantly differ (p > 0.05). Conclusions. The study indicated that badminton athletes' visual whole-body reaction speed was found to be better compared to their audio whole-body reaction speed ability. Additionally, Olympic athletes demonstrated enhanced strength conditions than regional and national-level athletes. The findings of this study are anticipated to help coaches in developing and implementing training programmes appropriate to the specific needs and conditions of athletes at the level of competition in which they are engaged.